All aboard the metro rail? : LTMRHL's campaign for stakeholder support - Kaul, Asha, (SAGE Knowledge. Cases., 2015)
On March 6, 2015 the Brand Ambassador campaign had completed a little over two years. Launched in 2013 to bring about awareness and dispel negativity about the Metro Rail project, this campaign had succeeded in securing visibility and garnering support. The corporate communication team was now debating the feasibility of the ongoing campaign and exploring various options. Based on the current review, a decision had to be taken to continue or abandon the campaign post commercial operations scheduled in July 2017. The campaign was launched in Hyderabad on January 8, 2013 through a press conference. The launch generated excitement and in the first week itself, there was a surge to register for the campaign. However, the intensity staggered post the felicitation ceremony on November 23, 2013. Queries related to the success and sustainability of the campaign were raised by multiple stakeholders. A two-year review in 2015 revealed that although many of the initial problems had been overcome, and negativity considerably reduced, the campaign had only achieved partial success. Will the current strategy be the gateway to success once commercial operations began, mulled Mr. Sanjay Kapoor, General Manager & Head Corporate Communications, PR & Advertising Business, L&T Metro Rail Hyderabad Ltd. (LTMRHL).